Full-time Work Determinants in Rural Urban Fringe - Yunisvita, Yunisvita; Zainal Ridho, Sari Lestari; Yulianita, Anna (International Journal of Economics and Financial Issues, 2017)
The purpose of this study is to analyze the determinants of employment opportunities in the RUF area in devoting more than 35 hours per week (full time). The survey is conducted on 326 labor samples determined by proportional random sampling method. Using the binomial logistic regression model of socio-economic variables, it is found that gender differences and the number of assets possessed have a significant effect on the magnitude of full-time employment opportunities. Whereas other socio-economic variables such as age, education and income showed a statistically insignificant effect. Keywords: Rural Urban Fringe, Logistic Regression, Socio-economics, full-time works. JEL Classifications: J20, J22